Bronze Age and Later Vegetation History on the Limestone Tabular Hills of North-East Yorkshire, UK: Pollen Diagrams from Dalby Forest. (1st January 2021) - Simmons, Ian; Innes, Jim; Appleyard, Anne; Ryan, Peter
Abstract: This paper presents the results of palynological investigations on the limestone Tabular Hills of the North York Moors in north-east England. These limestone areas have the highest concentration of post-Mesolithic archaeological sites in this upland region, but because of the geology and paucity of suitable organic deposits they have had almost no palynological research with which to assess the land-use history of these cultures, nor their impacts on the vegetation. This lack of palaeoecological information from the Tabular Hills has been addressed, so that the area's environmental history can be added to that of the rest of the North York Moors, which is relatively well known. Three pollen profiles have been examined, Yondhead Rigg providing an early Bronze Age to post-Medieval record, Seavy Slack providing a late Iron Age to post-Medieval record, and Dargate Dykes providing a late Medieval to modern record. The combined vegetation history from the three sites indicates a similar story to that from elsewhere on the Moors, with substantial forest disturbance in Bronze Age and Iron Age times, with significant woodland regeneration after each, but with the first main forest clearance phase for agriculture occurring during the Romano-British period, followed by early Medieval woodland regeneration, then extensive clearance in the later Medieval period for some arable cultivation and extensive animal husbandry on the rich calcareous grassland. In each agricultural phase the scale and intensity of disturbance seems to have been greater in these fertile limestone areas than in the rest of the Moors, with their poorer, more acidic soils, but still with an emphasis on stock-rearing and less extensive cultivation. The results will allow a more comprehensive landscape history of the North York Moors to be understood for later prehistory and more recent times.